The relative performance of real estate marketing platforms: MLS versus FSBOMadison.com - Igal Hendel; Aviv Nevo; François Ortalo-Magné (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2007)
We compare outcomes obtained by sellers who listed their home on a newly developed For-Sale-By-Owner (FSBO) web site versus those who used an agent and the Multiple Listing Service (MLS). We do not find support for the hypothesis that listing on the MLS helps sellers obtain a signi.cantly higher sale price. Listing on the MLS shortens the time it takes to sell a house. The diþusion of the new FSBO platform was quick, with the market share stabilizing after 2 years, suggesting it managed to gain a critical mass necessary to compete with the MLS. However, the lower eþectiveness of FSBO (in terms of time to sell and probability of a sale) suggests that the increasing returns to network size are not fully exploited at its current size. We discuss the welfare implications of our findings.
Keywords: 330; Immobilienmarkt; Immobilienmakler; Innovation; Internet; Wohlfahrtseffekt; USA